Diamonds and Emotions in the Minerals Gallery: Civilizing Emodities in the Age of Liberal Empire - Danielle Kinsey (Museum & Society, 2024)
This article examines discourse about diamonds and affect in London’s major geological and mineralogical galleries in the nineteenth century. While these institutions offered services to industries built around mineral extraction, their exhibition galleries also did important cultural work to promote the value of specific minerals to consumer publics. I argue that the metropolitan space of mineralogical exhibits was understood to create a tempered, and thus ‘civilized,’ emotional experience for visitors. In general consumer culture, diamonds were understood as emotional commodities (emodities) that derived value from both marking and eliciting heightened emotions; knowing this, the minerals galleries trustees offered the public a place to engage with diamonds in a ‘sobering’ manner. Gallery designers encouraged visitors to trade their whimsically romantic feelings about diamonds with ‘interested,’ patriotic ones. Galleries did this by promoting the idea that diamonds were intrinsically interesting and objectively superior minerals that deserved special scientific attention for the good of the nation-empire. By extension, diamonds also merited their high market value and national-imperial investment. Mineral galleries rationalized the diamond market for consumers by scientifically validating diamonds as emodities; diamonds also worked to animate mineral galleries as spaces of heritage-making in London. That legacy continues today.